UNIVERSAL VALUES IN THE TEACHINGS OF MIDDLE EASTERN THINKERS AND THEIR ROLE IN TECHNOLOGICAL EDUCATION - Mirsaidova Mubarak (Western European Studies, 2024)
Today, one of the most important problems is the development of labor education among students, thereby increasing students' respect for people's work, and awakening their love for nature. It has been mentioned that labor education has an important place in the education of children even in the works of our Eastern scholars. This article talks about the role of labor education in child development, views of labor education, science of technology in primary education today and the contribution of Eastern scholars to it.
Keywords: Eastern thinkers; Qobusnoma; craft; Firdavsi